Hospital’s Legal Responsibility in Health Services during the Covid-19 Pandemic - Elli Ruslina (LEGAL BRIEF, 2022)
Hospital is a health service institution that provides complete individual health services (health services that include promotive, preventive, curative, and rehabilitative services) that provide inpatient, outpatient, and emergency services. Health law is all legal provisions that are directly related to the maintenance or service of health and its application. This means that health law is a written rule regarding the relationship between the health service provider and the community or community members. By itself this health law regulates the rights and obligations of each service provider and service recipient or the community, either as individuals (patients) or community groups. The purpose of the study was to determine the legal responsibilities related to patient rights; legal responsibilities related to obligations set by the government; and legal responsibilities related to the task of carrying out the legislation. The research method uses analytical descriptive with a normative juridical approach, which uses secondary data in the form of legislation and research results. The conclusion is that legal responsibility for patient rights is the same as in general responsibilities, legal liability is classified into civil and criminal liability, and the responsibility is based on statutory provisions.